New Processes Working towards a Sustainable Society - Show, Pau Loke; Chew, Kit Wayne; Berenjian, Aydin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A change from a consumer society to a sustainable and conserver society must focus on for the welfare of the planet and future generations through balance rather than by maximizing the exploitation of resources. This will bring about further growth as an option for both per capita consumption and the population. Muddled and tepid responses make it clear that the society has not developed a vision of what a truly sustainable society looks like. It is essential to bring awareness to the possibility of creating a sustainable society which will incorporate sustainable development goals (SDGs) to generate a future with more possibilities. In order to move towards a sustainable society, it is vital to provide the highest standard of wellbeing, from an environmental, human, and economic perspective. We can contribute by providing technical and scientific studies that can be accessed freely and implemented by all. These works cover the important parameters that can be addressed to achieve sustainability, such as being energetically sustainable, resource-sustainable, environmentally sustainable, fiscally sustainable, and socially sustainable.